The effect of pituitary neuroendocrine tumors on the volumes of intracranial structures - Gökoğlu, Abdulkerim; Yiğit, Hüseyin; Yolaçan, Ebru; Nisari, Mehtap; Unur, Erdoğan; Selçuklu, Ahmet (Frontiers in Neurology, 2025)
ObjectivePituitary Neuroendocrine Tumors (PitNETs) can cause symptoms via mass effect or hormonal imbalances. This study investigated whether PitNETs induce volumetric changes in intracranial structures and assessed the diagnostic potential of these changes.Materials and methodsA retrospective analysis was conducted on 90 PitNET patients and 86 healthy controls. MRI data, acquired on a 1.5 Tesla scanner, were processed using the automated Vol2Brain system to calculate relative brain volumes.ResultsPitNET patients exhibited significantly lower relative volumes across numerous brain structures compared to controls. This included reduced intracranial, cerebral, and cortical gray matter (GM), as well as temporal lobe, vermis, limbic lobe, hippocampus, and inferior lateral ventricle (ILV) volumes. Gyrus-level analysis also revealed significantly smaller volumes in key regions like the posterior orbital gyrus, supplementary motor cortex, and entorhinal area in PitNET patients. ROC analysis demonstrated good to very good diagnostic performance for ILV volume (AUC = 0.863; p = 0.002) and subcortical GM volume (AUC = 0.725; p = 0.049) in differentiating groups. Reduced volumes were also noted in basal ganglia structures.ConclusionOur findings indicate significant volumetric reductions in various brain regions in PitNET patients, potentially explaining observed emotional and cognitive symptoms. The diagnostic utility of ILV and subcortical GM volumes is promising, suggesting their value as diagnostic adjuncts. These objective volumetric assessments may assist in surgical planning and patient stratification, though further prospective research is warranted to establish direct links with clinical outcomes.